2021
DOI: 10.1590/0102-77863620121
|View full text |Cite
|
Sign up to set email alerts
|

Produção e Qualidade de Melões Sob Diferentes Arranjos do Sistema de Irrigação e Coberturas do Solo

Abstract: Resumo Objetivou-se com este trabalho avaliar aspectos produtivos e de qualidade de meloeiros (Cucumis melo L.) sob diferentes formas de cultivo em Petrolina/PE durante dois ciclos produtivos. Adotou-se delineamento experimental de blocos casualizados com parcelas subsubdivididas em esquema fatorial 2 x 2 x 3, sendo, dois híbridos de melão amarelo (Gladial e SF 10/00 F1) nas parcelas, dois arranjos do sistema de irrigação (uma e duas fileiras de gotejadores por fileira de plantas) nas subparcelas, e três tipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
1
0
2
Order By: Relevance
“…DANTAS (2010) used a white mantle and found that the air and soil temperature decreased in the management of watermelon. Pereira et al, (2021) found superior results, using black and gray mulching compared to the soil discovered in the productive aspects of Gladial melon. Its use takes place in the form of tunnels after the transplantation of seedlings until the beginning of flowering.…”
Section: General Introductionmentioning
confidence: 94%
“…DANTAS (2010) used a white mantle and found that the air and soil temperature decreased in the management of watermelon. Pereira et al, (2021) found superior results, using black and gray mulching compared to the soil discovered in the productive aspects of Gladial melon. Its use takes place in the form of tunnels after the transplantation of seedlings until the beginning of flowering.…”
Section: General Introductionmentioning
confidence: 94%
“…These changes result in reduced accumulation and distribution of photoassimilates [9] and can compromise fruit yield and quality [10]. On the other hand, excess soil moisture can cause problems such as oxygen deficiency and increased disease incidence, leading to reduced productivity [11]. In this context, evaluating the physiological characteristics of watermelon crops under water restriction is important to understand the factors influencing the production of this vegetable under adverse conditions, especially in the Alagoas region, in which studies on this topic are still incipient.…”
Section: Introductionmentioning
confidence: 99%
“…These changes culminate in decreased accumulation and distribution of photoassimilates (S. S. Soares et al, 2023), potentially compromising production and fruit quality (Melo et al, 2022). On the other hand, excessive soil moisture can induce issues such as oxygen deficiency and disease incidence, further jeopardizing yields (Pereira et al, 2021).…”
Section: Introductionmentioning
confidence: 99%